Safety Considerations When Working with Humanized Animals. (12th December 2018) - Villano, Jason S; Vleck, Susan E; Felt, Stephen A; Myers, Daniel D; Lester, Patrick A
Abstract: Research using laboratory animals has been revolutionized by the creation of humanized animal models, which are immunodeficient animals engrafted with human cells, tissues, or organs. These animal models provide the research community a unique and promising opportunity to mimic a wide variety of disease conditions in humans, from infectious disease to cancer. A vast majority of these models are humanized mice like those injected with human CD34+ hematopoietic stem cells and patient-derived xenografts. With this technology comes the need for the animal research enterprise to understand the inherent and potential risks, such as exposure to bloodborne pathogens, associated with the model development and research applications. Here, we review existing humanized animal models and provide recommendations for their safe use based on regulatory framework and literature. A risk assessment program—from handling the human material to its administration to animals and animal housing—is a necessary initial step in mitigating risks associated with the use of humanized animals in research. Ultimately, establishing institutional policies and guidelines to ensure personnel safety is a legal and ethical responsibility of the research institution as part of the occupational health and safety program and overall animal care and use program.